Efficacy and mechanism of acupuncture for functional constipation in older adults: study protocol for a randomized controlled trial - Huai, Yisheng; Fan, Qian; Dong, Yiyue; Li, Xu; Hu, Junwei; Liu, Lumin; Chen, Yuelai; Yin, Ping (Frontiers in Neurology, 2024)
Introduction: Functional constipation (FC) is a common functional gastrointestinal disorder in clinical practice, with the prevalence of which increasing with age. Acupuncture is effective and recommended for the treatment of FC. However, little is known about how acupuncture affects the gut microbiota and inflammatory cytokines and thus improves gut function. Meanwhile, there are few high-quality clinical trials specifically focusing on acupuncture in treating FC in older people. The objective of this study is to assess the efficacy and safety of acupuncture in treating FC in older people. Additionally, the research aims to explore the mechanism of action of acupuncture in treating FC in older people by affecting intestinal microbiota and inflammation cytokines.This study is designed as a single-center, randomized, sham-controlled clinical trial. A total of 98 eligible FC patients will be randomized in a 1:1 ratio into an acupuncture group and a sham acupuncture group. Both groups will receive 24 treatments over 8 weeks with a 12-week followup. The primary outcome of the study is the treatment response rate, which is the proportion of participants with ≥3 mean weekly Complete Spontaneous Bowel Movements (CSBMs) over weeks 3-8. The secondary outcomes will include the proportion of participants with ≥3 mean weekly CSBMs during other assessment periods; the percentage of patients with ≥1 increase in mean weekly CSBMs from baseline; the average changes in CSBMs; Patient Assessment of Constipation-Symptoms (PAC-SYM), Bristol Stool Scale, Patient Assessment of Constipation Quality of Life Questionnaire (PAC-QOL), Self-rating Anxiety Scale (SAS), Self-rating Depression Scale (SDS) and weekly usage of emergency bowel medications. Adverse events will be recorded throughout the study. Data for the outcomes will be collected at Week 0 (baseline), Week 4 (the intervention period), Week 8 (the posttreatment), Week 12 (the follow-up period) and Week 20 (the follow-up period). In addition, changes in intestinal microbiota will be analyzed using 16S rDNA high-throughput detection, and the concentration of relevant inflammatory cytokines in serum will be measured by ELISA based on blood samples. The intention-to-treat analysis will be performed in this study.Trial registration: This trial has been registered in the China Clinical Trials Registry (registration number: ChiCTR2300070735).